Proceedings of SPE Annual Technical Conference and Exhibition 2007
DOI: 10.2523/110696-ms
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Horizontal Hydraulic Fracture at Depth Due to Stress Rotations Across a Thrust Fault

Abstract: fax 01-972-952-9435. AbstractMicroseismic imaging of a hydraulic fracture stimulation showed significant fracture reorientation across a thrust fault. Fracture orientations were identified through a combination of alignment of event locations, polarization of the seismic waves and injection details. Stimulation below the fault indicated a near horizontal fracture geometry. Above the fault, a near vertical fracture geometry was observed. A change in fault orientation was supported by differences in the microsei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In addition, in-situ stress state change due to geological movements (e.g. a thrust fault) (Maxwell et al 2007), secondary or enhanced oil recovery (Wright et al 1997;Wong and Chau 2004) may result in significant growth of horizontal fractures during fracturing. Daal and Economides (2006) studied hydraulically fractured wells in square and rectangular patterns, and they concluded that a dimensionless fracture conductivity of 1.6 will yield the highest productivity for production systems with proppant number below 0.1.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in-situ stress state change due to geological movements (e.g. a thrust fault) (Maxwell et al 2007), secondary or enhanced oil recovery (Wright et al 1997;Wong and Chau 2004) may result in significant growth of horizontal fractures during fracturing. Daal and Economides (2006) studied hydraulically fractured wells in square and rectangular patterns, and they concluded that a dimensionless fracture conductivity of 1.6 will yield the highest productivity for production systems with proppant number below 0.1.…”
Section: Introductionmentioning
confidence: 99%
“…Microseismicity can be used to track fracture geometry, height, length, and complexity, and be used to assess if the stimulation has interacted with a geohazard 1,2,3,4 . In order to realize the production potential of a horizontal well, it is necessary to maximize reservoir contact through properly designed stimulations 3 .…”
Section: Introductionmentioning
confidence: 99%